2017
DOI: 10.3945/ajcn.116.145607
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and calcium intake and risk of early menopause ,

Abstract: Background: Early menopause, defined as the cessation of ovarian function before the age of 45 y, affects w10% of women and is associated with higher risk of cardiovascular disease, osteoporosis, and other conditions. Few modifiable risk factors for early menopause have been identified, but emerging data suggest that high vitamin D intake may reduce risk. Objective: We evaluated how intakes of vitamin D and calcium are associated with the incidence of early menopause in the prospective Nurses' Health Study II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 44 publications
1
48
0
2
Order By: Relevance
“…Influence of menopause on functions of endocrine, cardiovascular, skeletal, immune, and genitourinary systems has been reported previously [2]. The age of menopause is affected by many factors including genetic factors, obesity, alcohol consumption, social levels, ethnicity, education, diet, vitamin D and calcium intake, menarche age, long-term menstrual cy-cles, oral contraceptive use, and exposure to pesticides [1][2][3][4]. The World Health Organization has stated that by the year 2030, globally, there will be more than 1.2 billion women suffering from menopause along with obesity and high body mass index (BMI) and moreover it has been reported that every year 47 million women enter this stage of their lives [1].…”
Section: Introductionmentioning
confidence: 94%
“…Influence of menopause on functions of endocrine, cardiovascular, skeletal, immune, and genitourinary systems has been reported previously [2]. The age of menopause is affected by many factors including genetic factors, obesity, alcohol consumption, social levels, ethnicity, education, diet, vitamin D and calcium intake, menarche age, long-term menstrual cy-cles, oral contraceptive use, and exposure to pesticides [1][2][3][4]. The World Health Organization has stated that by the year 2030, globally, there will be more than 1.2 billion women suffering from menopause along with obesity and high body mass index (BMI) and moreover it has been reported that every year 47 million women enter this stage of their lives [1].…”
Section: Introductionmentioning
confidence: 94%
“…Purdue-Smithe et al, 2017 (23) Prospective, 116,430 Vitamin D, calcium intake from dairy and non-dairy sources Vitamin D from dairy sources Calcium from dairy sources…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…), is enhanced by vitamin D deficiency (Purdue‐Smithe et al . ), i.e., menopause occurs earlier in those women that are deficient in vitamin D. There is also considerable evidence to indicate that vitamin D deficiency is related to mortality (Schöttker et al . ; Gaksch et al .…”
Section: Introductionmentioning
confidence: 99%